Bim, Bak, and Bax Regulate Osteoblast Survival - Liang, Min (2008)
INTRODUCTION: Osteoblasts depend on a constant supply of prosurvival signals from their microenvironment. When trophic factors become limited by injury or disease, cells undergo apoptosis. This study establishes the regulation and function of Bim, Bak, and Bax in this response. MATERIALS AND METHODS: MBA-15.4 murine osteoblasts and primary human bone marrow stromal cells (hBMSCs) were subjected to growth factor depletion by serum starvation (1% FCS or serum withdrawal). Protein phosphorylation, activation, or expression was quantified by Western blotting and gene expression by real-time PCR. Regulation of apoptosis in response to serum depletion was determined using siRNA specific for Bim, Bak, or Bax, followed by TUNEL staining. Statistical significance was determined by one-way ANOVA after multiple experimental repeats. RESULTS: Serum depletion strongly induced expression of the proapoptotic protein Bim in both hBMSC and MBA-15.4 osteoblasts. Detailed analysis of the mouse line showed that both mRNA and protein levels rose from 2 h to peak between 16 and 24 h, in conjunction with activation of caspase 3 and rising levels of apoptosis. Both actinomycin D and cycloheximide prevented this increase in Bim, indicating transcriptional regulation. Serum deprivation caused immediate and sustained decreases in phosphorylation of prosurvival kinases, ERK and PKB, preceding upregulation of Bim. Pathway inhibitors, U0126 or LY294002, strongly increased both Bim mRNA and protein, confirming that both kinases regulate Bim. These inhibitors also induced osteoblast apoptosis within 24–72 h. JC-1 tracer detected mitochondrial potential disruption after serum deprivation, indicating involvement of the intrinsic pathway. Moreover, activation-associated conformational changes were detected in the channel-formers, Bax and Bak. Selective knockdown of Bim or Bak by siRNA protected osteoblasts from serum depletion-induced apoptosis by 50%, whereas knockdown of Bax alone or Bak and Bax together reduced apoptosis by 90%. CONCLUSIONS: Our data indicate that Bim, Bak, and Bax actively mediate osteoblast apoptosis induced by trophic factor withdrawal. The complex upstream regulation of Bim may provide targets for therapeutic enhancement of osteoblast viability.